El papel de la familia en el desarrollo de la regulación emocional en adolescentes - Manzanillas Jumbo, María José (2025)
The family constitutes children develop the ability to manage emotions, an essential skill for their well-being and balance. The environment in which they grow up and the relationships they establish with their reference figures determine how they learn to regulate their emotions and face everyday challenges. This study focused on identifying the factors in the family environment that promote emotional regulation in adolescents and establishing appropriate emotional regulation strategies in the function of the environment. The study was conducted under a mixed approach, cross-sectional, non-experimental, descriptive design, exploratory and correlational scope; through the systematic review technique. The sample consisted of 10 scientific articles (6 280 participants), from countries such as Ecuador, Peru, Mexico, the United States, Spain, and China; documents extracted from Pubmed, Springer Link, Dialnet and Redalyc. The results highlighted the quality of family relationship, constant support, cohesion, effective communication, clarity in roles and functions, as well as the application of appropriate strategies such as cognitive reappraisal and mindfulness, constitute fundamental pillars to enhancing adolescents’ emotional skills. A healthy family environment encourages emotional regulation and contributes to strengthening resilience and adaptation to challenges typical of this stage. Consequently, this research reaffirmed the importance of building enriching family spaces that promote the comprehensive emotional growth of adolescents, consolidating the family as an indispensable factor for their full and healthy development